Intrafraction motion and impact of margin reduction for MR‐Linac online adaptive radiotherapy for pancreatic cancer treatments - Ashleigh Fasala; Madeline Carr; Yolanda Surjan; Parmoun Daghigh; Jeremy deLeon; Abbey Burns; Vikneswary Batumalai (Journal of Medical Radiation Sciences)
Abstract Introduction Online adaptive radiotherapy is well suited for stereotactic ablative radiotherapy (SABR) in pancreatic cancer due to considerable intrafractional tumour motion. This study aimed to assess intrafraction motion and generate adjusted planning target volume (PTV) margins required for online adaptive radiotherapy in pancreatic cancer treatment using abdominal compression on the magnetic resonance linear accelerator (MR‐Linac). Methods Motion monitoring images obtained from 67 fractions for 15 previously treated pancreatic cancer patients were analysed. All patients received SABR (50 Gy in five fractions) on the MR‐Linac using abdominal compression. The analysis included quantification of intrafraction motion, leading to the development of adjusted PTV margins. The dosimetric impact of implementing the adjusted PTV was then evaluated in a cohort of 20 patients. Results Intrafraction motion indicated an average target displacement of 1–3 mm, resulting in an adjusted PTV margin of 2 mm in the right–left and superior–inferior directions, and 3 mm in the anterior–posterior direction. Plans incorporating these adjusted margins consistently demonstrated improved dose to target volumes, with improvements averaging 1.5 Gy in CTV D99%, 4.9 Gy in PTV D99% and 1.2 Gy in PTV‐high D90%, and better sparing of the organs at risk (OAR). Conclusions The improved target volume coverage and reduced OAR dose suggest potential for reducing current clinical margins for MR‐Linac treatment. However, it is important to note that decreasing margins may reduce safeguards against geographical misses. Nonetheless, the continued integration of gating systems on MR‐Linacs could provide confidence in adopting reduced margins.